Hosea-Micah - Goldingay, John, autor (Baker commentary on the Old Testament: prophetic books, 2021)
"A highly regarded Old Testament scholar offers a substantive and useful commentary on Hosea-Micah and explores the contemporary significance of these prophetic books"--